Comparative analysis of the exosomal contents of DF-1 cells infected by ALV-J - Jie Yang; Pingping Zhuang; Ziqiang Cheng; Guihua Wang (Veterinární Medicína, 2022)
Exploration of the abnormal expression of exosomal molecules during the infection of avian leukosis virus subgroup J (ALV-J) is essential to provide a deeper understanding of the exosome's role in the viral pathogenesis involved. The study aimed to investigate the differentially expressed proteins and miRNAs of the exosomes derived from DF-1 cells infected by ALV-J, their gene function and involved signal pathways. We isolated exosomes from DF-1 cells infected by ALV-J. The differentially expressed proteins and miRNAs of the exosomes were determined by proteomics and transcription detection technology. A Gene Ontology (GO) analysis and a Kyoto Encyclopedia of Genes and Genomes (KEGG) signal pathway analysis identified the miRNAs target genes and the signal pathways regulated by the different proteins or/and miRNAs. A total of 116 proteins (58 upregulated and 58 downregulated) and 3 miRNAs (all upregulated) were determined. These proteins were involved in 155 signal pathways, in which the highest number of proteins involved in the cancer pathway was (up to) seven. The target genes of the miRNAs were involved in 3 signal pathways. Both the proteins and target genes of the miRNAs were involved in the Ribosome pathway and ECM-receptor interaction pathway. The results suggested that the ALV-J infection changed the proteins and miRNAs of the exosomes significantly.